PENGGUNAAN MEDIA PRESENTASI DALAM MENINGKATKAN DAYA INGAT SISWA/SISWI SEKOLAH DASAR - Letek, Maria Rosari; Permana, Natalis Sukma (CREDENDUM: Jurnal Pendidikan Agama, 2023)
This research aims to improve elementary school students' memory by using learning presentation media, which was carried out at SDK Karitas 2 Surabaya using the Kemmis and Tanggart Model. This research method uses Classroom Action Research (PTK). This research was carried out in 2 cycles using the Catholic Religious Education subject as an example and using different materials. The subjects of this Classroom Action Research were class III students at SDK Karitas 2 Surabaya with a total of 35 students. 22 male students and 13 female students. This research instrument uses observation, interviews, written tests and documentation. Data analysis uses qualitative and quantitative descriptive analysis. The results of this research have been able to improve students' memory by using the Kemmis and Tanggart Model learning presentation media, which consists of four components, namely, Planning, Acting, Observing, Reflecting. This increase can be seen in the Pre-Cycle, namely 75.2%, then in Cycle I 88% and in Cycle II it rose to 98%.